1985
DOI: 10.1002/jcu.1870130704
|View full text |Cite
|
Sign up to set email alerts
|

Significance of preoperative use of ultrasonography in parathyroid neoplasms: Comparison of sonographic textures with histologic findings

Abstract: The sonographic textures of 10 parathyroid tumors in nine patients were examined and compared with their histologic features, particularly with the amount of fibrous trabeculae. The carcinomas containing a large amount of fibrous trabeculae, which is the most frequent finding in parathyroid cancer, were very echogenic. On the other hand, the adenomas without fibrous trabeculae showed a low echogenicity. These data suggest that the possibility of malignancy is high when the parathyroid tumor is found to be very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 6 publications
1
4
0
1
Order By: Relevance
“…In addition, Kinoshita et al reported that a parathyroid tumor with high echogenicity is more likely to be a carcinoma than an adenoma [16]. However, Edmonson et al and Daly et al did not support this conclusion [17,18], and our findings are consistent with those reported by these authors.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, Kinoshita et al reported that a parathyroid tumor with high echogenicity is more likely to be a carcinoma than an adenoma [16]. However, Edmonson et al and Daly et al did not support this conclusion [17,18], and our findings are consistent with those reported by these authors.…”
Section: Resultssupporting
confidence: 88%
“…Interestingly, two of the three adenomas with a DW ratio >_ 1 were associated with either chronic thyroiditis or thyroid tumor, and the third adenoma did not lie beneath the thyroid gland. DW ratio = D (depth)/W (width) accounting for fewer than 1 % of cases of primary hyperparathyroidism, literature regarding its ultrasonographic features is limited [16][17][18][19]25]. Moreover, previous reports included relatively few cases of parathyroid carcinoma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…isiknowledge.com/). This identified a total of 2 further studies, giving a total of 15 studies [15,16,[18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Ultrasound Criteria and Blinded Reviewmentioning
confidence: 99%
“…Beim Überwiegen fibröser Tumoranteile, evtl. auch in Abhängig-keit von der Schallfrequenz (3,5 MHz Real-time-linear Scanner), wurden auch gleichmäßig echoreich erscheinende Echomuster, ähnlich des angrenzenden Schilddrüsenparenchyms, beschrieben[25]. Beim Einsatz hochfrequenter Real-time-Sonographie-Geräte (7,5 -10 MHz) lag der durchschnittliche Durchmesser der Nebenschilddrüsenkarzinome bei 2,4 cm bei rundlicher oder ovoider Form und lobulierter Randkontur.…”
unclassified